The Artistic-Staging Solution of a Ballet Performance and its Assessment (by the Examples from the Legacy of S. Diaghilev’s "Russian Seasons") - Portnova, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes the main components of an artistic-figurative concept in the staging solution of a ballet performance. The artistic style is considered as a sign characterized by general significance; as a universal category of choreography functioning at all levels of the organization of the stage system. The results of the analysis of a number of ballet performances of the Russian theatrical concern of a well-known theatrical and art personality S. P. Diaghilev (1872-1929) are presented. The interrelation of figurativeness and expressiveness in the contemporary dance space generates new approaches to understanding, studying and assessing ballet art.